2022
DOI: 10.1021/acs.analchem.2c03766
|View full text |Cite
|
Sign up to set email alerts
|

Dense Conductive Metal–Organic Frameworks as Robust Electrocatalysts for Biosensing

Abstract: Due to the fascinating properties such as high porosity, large surface areas, and tunable chemical components, metal–organic frameworks (MOFs) have emerged in many fields including catalysis, energy storage, and gas separation. However, the intrinsic electrical insulation of MOFs severely restricts their application in electrochemistry. Here, we synthesize a series of 2D conductive MOFs (cMOFs) through tuning the structure with atomic precision using simple hydrothermal methods. Various electroactive probes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…32 The other peak at 1621 cm −1 corresponded to C�O in polyvinylpyrrolidone, which was introduced during CuONFs fabrication process. 15,33 As for NH 2 −CuONFs (curve b), two new adsorption peaks near 2928 and 2863 cm −1 represented the stretching vibration of C−H of amination reagent (APTES). Two enhanced peaks were observed at 1550 and 1656 cm −1 , respectively, corresponding to N−H stretch in APTES, implying the successful preparation of NH 2 −CuONFs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…32 The other peak at 1621 cm −1 corresponded to C�O in polyvinylpyrrolidone, which was introduced during CuONFs fabrication process. 15,33 As for NH 2 −CuONFs (curve b), two new adsorption peaks near 2928 and 2863 cm −1 represented the stretching vibration of C−H of amination reagent (APTES). Two enhanced peaks were observed at 1550 and 1656 cm −1 , respectively, corresponding to N−H stretch in APTES, implying the successful preparation of NH 2 −CuONFs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Finally, tunable active centers enable the selective detection of target analytes. [237,239] Currently, research on the sensing performance of conductive MOFs mainly focuses on selectivity, sensitivity, and response speed.…”
Section: Conductive Mofs For Electrochemical Sensorsmentioning
confidence: 99%
“…developed a Cu‐THQ‐based sensor with an ultra‐low detection limit for paraoxon and revealed the structure‐property relationship of Cu‐THQ. [ 239 ] The research found that compared to other conductive MOF‐based sensors, the Cu‐THQ‐based sensor exhibited significantly improved electrocatalytic performance at lower potentials. Mechanistic investigations revealed that this enhanced electrocatalytic performance can be attributed to more efficient charge transfer interactions between the dense catalytic sites of Cu‐THQ and the analyte.…”
Section: Electrochemical Application Of Conductive Mofsmentioning
confidence: 99%
“…Fabrication of the PEC Biosensor. First, the pretreated glassy carbon electrode (GCE) 31 was dipped into 0.25% (w/v) HAuCl 4 for electrostatic deposition of gold nanoparticles (depAu). Then, 10 μL of 2 μM HP was dropped onto the GCE and incubated at 4 °C for 12 h. Following that, hexanethiol (HT, 10 μL of 0.1 mM) was reacted for 40 min to block the nonspecific reaction sites.…”
Section: ■ Introductionmentioning
confidence: 99%